Enforcement of Legal Sanctions Against Environmental Pollution Violations Caused by Natural Stone Business Waste in Cirebon Regency - Susanti, Susanti; Rizkha, Ikrima Istiqomah; Sa'diyah, Ghina; Harmono , Harmono; Permana , Deni Yusup (Journal of Legal and Cultural Analytics, 2025)
Developing the industrial and mining sectors, especially the natural stone business in Cirebon Regency, contributes significantly to regional economic growth. However, this activity poses serious problems related to environmental pollution due to the waste produced, both solid and liquid waste. If not managed properly, the garbage can pollute the environment and negatively impact public health and ecosystems. Despite the regulations on environmental protection, business actors who are not subject to strict sanctions create legal uncertainty and reflect the low effectiveness of the legal system. This study aims to evaluate the effectiveness of law enforcement and identify the factors that affect its success. The methodology includes normative juridical approaches and qualitative analysis through observation and interviews. The research shows the need for stricter policies to improve environmental law enforcement, strengthen supervision, develop WWTPs, and educate business actors and the community on sustainable practices. These policies are expected to create collective awareness supporting sustainable environmental conservation efforts. The effectiveness of enforcing legal sanctions against environmental pollution violations due to natural stone business waste in Cirebon Regency is still relatively low, even though there are normatively adequate regulations. Local governments strengthen the institutional capacity of law enforcement, especially the Environment Agency, through increasing the number and competence of human resources as well as adequate budget allocation for supervision and enforcement.